A Computational Analysis of the Intrinsic Plasticity of Five-Coordinate Cu(II) Complexes and the Factors Leading to the Breakdown of the Orbital Directing Effect in Paddlewheel Secondary Building Units - Alzahrani, Khalid A H (Journal of computational chemistry, 2020)
© 2019 Wiley Periodicals, Inc.